Evaluating the Role of the Dorsolateral Prefrontal Cortex and Posterior Parietal Cortex in Memory-Guided Attention With Repetitive Transcranial Magnetic Stimulation - Wang, Min; Yang, Ping; Wan, Chaoyang; Jin, Zhenlan; Zhang, Junjun; Li, Ling (Frontiers in Human Neuroscience, 2018)
The contents of working memory (WM) can affect the subsequent visual search performance, resulting in either beneficial or cost effects, when the visual search target is included in or spatially dissociated from the memorized contents, respectively. The right dorsolateral prefrontal cortex (rDLPFC) and the right posterior parietal cortex (rPPC) have been suggested to be associated with the congruence/incongruence effects of the working memory content and the visual search target. Thus, in the present study, we investigated the role of the DLPFC and the PPC in controlling the interaction between WM and attention during a visual search, using repetitive transcranial magnetic stimulation (rTMS). Subjects maintained a color in WM while performing a search task. The color cue contained the target (valid), the distractor (invalid) or did not reappear in the search display (neutral). Concurrent stimulation with the search onset showed that relative to rTMS over the vertex, rTMS over rPPC and rDLPFC further decreased the search reaction time, when the memory cue contained the search target. The results suggest that the rDLPFC and the rPPC are critical for controlling working memory biases in human visual attention.